A Note on the Concordance Invariant Epsilon. (17th July 2021) - Wang, Shida
Abstract: We compare the smooth concordance invariants Upsilon, phi and epsilon. Previous work gave examples of knots with one of the Upsilon and phi invariants zero but the epsilon invariant nonzero. We build an infinite family of linearly independent knots with both the Upsilon and phi invariants zero but the epsilon invariant nonzero. This provides examples of knots with arbitrarily large concordance genus but vanishing bounds from the Upsilon and phi invariants.